Nutritional intervention for diabetes mellitus with Alzheimer's disease - Li, Zhi; Li, Simian; Xiao, Ying; Zhong, Tian; Yu, Xi; Wang, Ling (Frontiers in Nutrition, 2022)
Background and Objectives: The combined disease burden of diabetes mellitus (DM) and Alzheimer's disease (AD) is increasing, and the two diseases share some common pathological changes. However, the pharmacotherapeutic approach to this clinical complexity is limited to symptomatic rather than disease arresting, with the possible exception of metformin. Whether nutritional intervention might extend or synergize with these effects of metformin is of interest. In particular, dietary patterns with an emphasis on dietary diversity shown to affect cognitive function are of growing interest in a range of food cultural settings, e.g. food cultures in the counties of Mediterranean and North East Asia. In this paper, cross-cultural nutritional intervention programs with the potential to mitigate both insulin resistance and hyperglycemia, together with cognitive impairment were reviewed. Methods: PubMed, EMBASE, Cochrane Library and China National Knowledge Infrastructure (CNKI) databases were searched to identify the relevant and reliable literatures up to June 2022. The following search terms were used: Alzheimer’s disease, diabetes, dementia, food ingredients, nutrition and diet. Results: Both of dietary patterns and nutritional supplementation showed the effects of improving glycemic control and reducing cognitive decline in diabetes associated with Alzheimer's disease, but the intervention specificity remained controversial. Multi-nutrient supplements combined with diverse diets may have preventive and therapeutic potential for DM combined with AD, at least as related to B vitamin group and folate-dependent homocysteine. Conclusions: Although nutritional intervention has promise in the prevention and management of DM and AD comorbidities, and more clinical studies would be of nutritional scientific merit, the dietary approaches with promise are in general those which are increasingly supported as cross-culturally healthful.